Transmission Jeopardy of Adenomatosis Polyposis Coli and Methylenetetrahydrofolate Reductase in Colorectal Cancer - Mohd, Younis; Kumar, Parvinder; Kuchi Bhotla, Haripriya; Meyyazhagan, Arun; Balasubramanian, Balamuralikrishnan; Ramesh Kumar, Mithun Kumar; Pappusamy, Manikantan; Alagamuthu, Karthick Kumar; Orlacchio, Antonio; Keshavarao, Sasikala; Sampathkumar, Palanisamy; Arumugam, Vijaya Anand (Journal of the Renin-Angiotensin-Aldosterone System, 2021)
Colorectal cancer (CRC) is one of the globally prevalent and virulent types of cancer with a distinct alteration in chromosomes. Often, any alterations in the adenomatosis polyposis coli (APC), a tumor suppressor gene, and methylenetetrahydrofolate reductase (MTHFR) gene are related to surmise colorectal cancer significantly. In this study, we have investigated chromosomal and gene variants to discern a new-fangled gene and its expression in the southern populations of India by primarily spotting the screened APC and MTHFR variants in CRC patients. An equal number of CRC patients and healthy control subjects (n=65) were evaluated to observe a chromosomal alteration in the concerted and singular manner for APC and MTHFR genotypes using standard protocols. The increasing prognosis was observed in persons with higher alcoholism and smoking (P<0.05) with frequent alterations in chromosomes 1, 5, 12, 13, 15, 17, 18, 21, and 22. The APC Asp 1822Val and MTHFR C677T genotypes provided significant results, while the variant alleles of this polymorphism were linked with an elevated risk of CRC. Chromosomal alterations can be the major cause in inducing carcinogenic outcomes in CRCs and can drive to extreme pathological states.